Blockchain-based Education Project - Guustaaf, Edward; Rahardja, Untung; Aini, Qurotul; Maharani, Herliana Wahyu; Santoso, Nesti Anggraini (Pandawan, 2021)
Blockchain is a jointly distributed and decentralized ledger, in which nodes are aiming to record transaction history with very different networks. This technology is quite practical if used in the field of higher education to carry out digital certification, record keeping, etc. From several papers published on this, no single paper covering educational projects based on the blockchain can find it. So there are the latest opportunities for higher education trends. Projects in the field of higher education that are blockchain-based are aimed at solving problems that occur in educators today. On that basis, we conclude that there is a need for a systematic literature review. Therefore, based on the education project, this study will review the artistic gap between the two. This paper will focus on the protocol used in this project and explore several blockchain-based higher education projects that will be the aim of this paper. As well as analyzing the blockchain features currently in use today and the services that will be offered by existing educational projects, to improve the implementation of technology in the field of education by using the blockchain feature.